2005
DOI: 10.1158/0008-5472.can-04-3654
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor–Related Protein Inhibits Cell Growth and Induces Apoptosis of BxPC3 Pancreatic Cancer Cells

Abstract: Dysregulation of the epidermal growth factor receptor (EGFR) signaling network has been frequently reported in pancreatic cancer. Inhibition of EGFR was associated with antitumor effects in both in vitro and in vivo studies of pancreatic cancer. We have previously reported the isolation and characterization of an EGFR-related protein (ERRP), which seems to be a negative regulator of EGFR. In the present investigation, we tested our hypothesis whether recombinant ERRP could be an effective inhibitor of growth o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 16 publications
4
33
0
Order By: Relevance
“…ERRP, a recently isolated pan-erbB inhibitor, possesses substantial homology with the extracellular ligandbinding domain of EGFR and its family members (8). Previously, we reported that ERRP inhibited cell growth of pancreatic cancer cells by attenuating EGFR activation in vitro and in vivo (13,14). Our current data show that ERRP not only inhibits cell growth but also induces apoptotic cell death of pancreatic cancer cells, similar observations in colon and breast cancer cells (24).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…ERRP, a recently isolated pan-erbB inhibitor, possesses substantial homology with the extracellular ligandbinding domain of EGFR and its family members (8). Previously, we reported that ERRP inhibited cell growth of pancreatic cancer cells by attenuating EGFR activation in vitro and in vivo (13,14). Our current data show that ERRP not only inhibits cell growth but also induces apoptotic cell death of pancreatic cancer cells, similar observations in colon and breast cancer cells (24).…”
Section: Discussionsupporting
confidence: 85%
“…ERRP fusion protein was generated using the Drosophila expression system (Invitrogen) as described previously, and silver staining of the SDS-PAGE resulted in a predominant protein band of M r 53 to 55 following purification (13,14). The protein band of M r 53 to 55 corresponded well with the calculated molecular mass of ERRP, which is composed of 479 amino acids.…”
Section: Methodsmentioning
confidence: 95%
“…Most importantly, ERRP was found to inhibit pancreatic tumor growth in a SCID mouse xenograft model. The anti-tumor activity of ERRP correlated well with down-regulation of NF-κB, MAPK, Akt, and Notch-1 (Wang et al, 2006b;Zhang et al, 2005;Zhang et al, 2006). ERRP also down-regulates NF-κB downstream genes such as VEGF and MMP-9, and inhibits cancer cell invasion, suggesting that ERRP could be a very potent agent for the treatment of pancreatic cancer by inhibiting cell survival signaling, tumor growth, invasion, and angiogenesis.…”
Section: New Strategies For the Treatment Of Pancreatic Cancers Targementioning
confidence: 83%
“…It remains to be determined if this difference is a time-dependent phenomenon, and whether a longer treatment period (more than the 10 days used in the present study) would result in down-regulation of other members of the EGFR family. However, the overexpression of EGFR in carcinogen-treated mucosa (29,38), ACF (32), and Min intestinal tissue (33) suggests that this receptor plays a crucial role in the development of colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we reported that increased activation of EGFR in the colonic mucosa of aged or carcinogen-treated rodents was associated with elevated levels of membrane-bound precursor forms of TGF-a (29,38), which was thought to be involved in activating the intrinsic EGFR activity through an autocrine/ juxtacrine mechanism (45,46). The substantial homology of ERRP to the extracellular ligand-binding domain of the EGFRs allows for sequestration of ligands, rendering them unavailable for binding to and activation of the receptors.…”
Section: Discussionmentioning
confidence: 99%